Menciptakan Solusi Inovatif untuk Mengatasi Tantangan dalam Pembelajaran Jarak Jauh: Studi Kasus Keterlibatan Siswa dan Aksesibilitas - Saadiah, Ai Dina; Kurniawan, Asep; Maesyaroh, Siti; Ultsa, Fachrudin; Nulhakim, Lukman; Hasani, Aceng (Jurnal Ilmiah Global Education, 2025)
Distance learning (DLE) has become an integral part of the global education system, especially with the advancement of technology and challenges such as the pandemic. However, DLE also faces several challenges, including low student engagement and accessibility issues. This paper aims to identify and analyze innovative solutions that can address these challenges. Through case studies and literature review, we explore strategies such as personalization of learning, use of interactive technologies, and inclusive approaches to increase student engagement and ensure equitable accessibility. The results show that a combination of these strategies can significantly improve the effectiveness of DLE.